A janus kinase from Scylla paramamosain activates JAK/STAT signaling pathway to restrain mud crab reovirus. Issue 90 (July 2019) - Deng, Hengwei; Xu, Xiaopeng; Hu, Lei; Li, Jingjing; Zhou, Dandan; Liu, Shanshan; Luo, Panpan; He, Jianguo; Weng, Shaoping
Abstract: JAK/STAT signaling pathways are associated with the innate immune system and play important roles in mediating immune responses to virus infection. In this study, a Janus kinase gene from Scylla paramamosain ( Sp JAK) was cloned and characterized. The full length of Sp JAK mRNA contains a 5′ untranslated region (UTR) of 304 bp, an open reading frame of 3300 bp and a 3′ UTR of 302 bp. The Sp JAK protein contains seven characteristic JAK homology domains (JH1 to JH7) and showed 60% identity (78% similarity), 20% identity (35% similarity), and 21% identity (37% similarity) to the Litopenaeus vannamei JAK ( Lv JAK) protein, the Drosophila melanogaster hopscotch protein, and the Homo sapiens JAK2 protein, respectively. The mRNA of Sp JAK showed high expression in the brain and nerve but low expression in the hemocyte and muscle. Moreover, the expression of Sp JAK was significantly upregulated by stimulation with mud crab reovirus (MCRV), poly(I:C), and Vibrio parahaemolyticus . Sp JAK significantly activated the STAT of S. paramamosain ( Sp STAT) to translocate to the nucleus of Drosophila Schneider 2 cells. Sp JAK significantly enhanced the activity of the promoter of the WSSV wsv069 gene that was activated significantly by Sp STAT by acting on the STAT-binding DNA motif. These results suggest that Sp JAK activates the JAK/STAT pathway. Furthermore, silencing Sp JAK in vivo resulted in the high mortality rate of MCRV-infected mud crabs and increased the viral load in tissues. Hence, Sp JAK could play an important role in defense against MCRV in mud crab. Highlights: The full length of Janus kinase gene from Scylla paramamosain ( Sp JAK) was cloned and characterized. The expression of Sp JAK was significantly upregulated by stimulation with mud crab reovirus (MCRV), poly(I:C). Sp JAK significantly activated Sp STAT to translocate to the nucleus of S2 cells. Sp JAK could activates the JAK/STAT pathway. Sp JAK could play an important role in defense against MCRV in mud crab.